2014
DOI: 10.1097/shk.0000000000000109
|View full text |Cite
|
Sign up to set email alerts
|

Thromboelastogram Evaluation of the Impact of Hypercoagulability in Trauma Patients

Abstract: Approximately a quarter of trauma patients presented in a hypercoagulable state. Hypercoagulable patients required less blood products, in particular plasma. They also had a lower 24-h and 7-day mortality and lower rates of bleeding-related deaths. Further evaluation of the mechanism responsible for the hypercoagulable state and its implications on outcome is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 29 publications
(14 reference statements)
3
45
0
Order By: Relevance
“…Only more recently have investigators identified a third acute hypercoagulable or activated hemostatic state as also existing in ED trauma patients. Branco et al found that coagulation activation was associated with less blood product transfusion and low mortality, and was therefore protective during the acute phase of trauma treatment [21]. Similarly, we also identified a small cluster of subjects (cluster 2) with an overall activated hemostatic response that required minimal hemostatic therapy during the acute phase of trauma treatment (i.e.…”
Section: Discussionsupporting
confidence: 75%
“…Only more recently have investigators identified a third acute hypercoagulable or activated hemostatic state as also existing in ED trauma patients. Branco et al found that coagulation activation was associated with less blood product transfusion and low mortality, and was therefore protective during the acute phase of trauma treatment [21]. Similarly, we also identified a small cluster of subjects (cluster 2) with an overall activated hemostatic response that required minimal hemostatic therapy during the acute phase of trauma treatment (i.e.…”
Section: Discussionsupporting
confidence: 75%
“…Branco et al [22] identified a hypercoagulable state in 26.3 % of trauma patients on admission using TEG parameters R, K, aA, MA, G, and EPL. Using rapid-TEG, a similar TEG assay using a faster activator than in standard TEG, Kashuk et al [23] identified 67 % of a cohort of critically ill patients to be hypercoagulable, based on G score.…”
Section: Discussionmentioning
confidence: 99%
“…The association of TBI and a hypercoagulable state is well established [5,7,10]; however, the onset and duration of the hypercoagulable state is not. Elevations in TEG parameters have been associated with a hypercoagulable state [21][22][23]. The purpose of this study was to identify a hypercoagulable state after TBI, as defined by elevations in TEG parameters: maximal amplitude (MA), thrombus generation (TG), G value (G), and alpha angle (aA).…”
Section: Introductionmentioning
confidence: 99%
“…To optimize prediction of massive transfusion risk, admission coagulopathy must, however, be interpreted in association with the lesional status and the presence of surgical bleeding source . PT point‐of‐care however cannot provide information on the entire coagulation process, contrary to viscoelastic tests (i.e., PLT and fibrinogen function, hyperfibrinolysis, or hypercoagulability status) . This device indeed assesses only part of the global function of coagulation cascade.…”
Section: Discussionmentioning
confidence: 99%
“…33 PT pointof-care however cannot provide information on the entire coagulation process, contrary to viscoelastic tests (i.e., PLT and fibrinogen function, hyperfibrinolysis, or hypercoagulability status). [14][15][16][17]39 This device indeed assesses only part of the global function of coagulation cascade. We have, however, shown in a previous series that fibrinogen deficit was reliably predicted using the admission PTr value.…”
Section: Discussionmentioning
confidence: 99%